Transition-metal free synthesis of N-aryl carbazoles and their extended analogs. Issue 33 (9th August 2021) - Feofanov, Mikhail; Akhmetov, Vladimir; Takayama, Ryo; Amsharov, Konstantin
Abstract : Herein, we describe a facile synthesis of N -heteroacenes via ladderization of fluorinated oligophenylenes. Abstract : Herein, we describe a facile synthesis of N -arylated carbazoles via ladderization of fluorinated oligophenylenes. The reaction consists of two subsequent nucleophilic substitutions triggered by an electronic transfer from dimsyl anions. The reaction allows the effective one-pot formation of at least six C–N bonds with pronounced selectivity to the C–F bond placement.